Andrés Rivera: la ética de hacer memoria - Waldegaray, Marta Inés (Anales de Literatura Hispanoamericana, 2008)
History is the material of Andrés Rivera´s narratives together with his leftist political ideas which have given them shape for over four decades. Nevertheless, his meticulous way of telling, more and more reticent and repetitive, masks the historic referent and nullifies the linear presentation of the story. The narrative present tense corrodes the story’s space-time coordinate system. The past keeps the symbolic place of ethical reservoir. Present tense and minimalist narrative are in Rivera’s fictions the way in which memory takes shape. They are also a way of resistance to the corrosion/corruption of the present times, fidelity to his political truth, and engagement for his conservation. We will analyze the whole work of Rivera, especially his work over the last forty years.